2014
DOI: 10.1021/ic4031206
|View full text |Cite
|
Sign up to set email alerts
|

Dinuclear Ru/Ni, Ir/Ni, and Ir/Pt Complexes with Bridging Phenanthroline-5,6-dithiolate: Synthesis, Structure, and Electrochemical and Photophysical Behavior

Abstract: We report the synthesis and full characterization of dinuclear complexes with the bridging ligand phenanthroline-5,6-dithiolate (phendt(2-)) featuring the [Ru(bpy)2](2+) or Ir(ppy)2](+) fragment at the diimine donor center and the [Ni(dppe)](2+) or [Pt(phen)](2+) complex moiety at the dithiolate group. The molecular structures of the mononuclear complexes [(C5H5)2Ti(S,S'-phendt)] and [(ppy)2Ir{N,N'-phendt-(C2H4CN)2}](PF6) as well as the dinuclear complex [(C5H5)(PPh3)Ru(phendt)Ni(dppe)](PF6) determined by X-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 107 publications
1
19
1
Order By: Relevance
“…Conspicuously, the orientation of the thiophene rings are distributed almost equally with 54 % and 46 % for parallel and antiparallel orientations, respectively. This is in contrast with literature value for related compounds favoring the parallel orientation with 75 % Taking the less steric demand of thiophene moieties within 2 into account, the measured torsion angles of the two thiophenes with 65.31° and 67.60° with respect to the phenanthroline plane seem reasonable, which is very similar to previously reported thiophene‐substituted phenanthrolines. Interestingly, in case of even more sterically demanding dimethyl‐substituted thiophenes torsion angles lie in the same region , …”
Section: Resultscontrasting
confidence: 61%
See 1 more Smart Citation
“…Conspicuously, the orientation of the thiophene rings are distributed almost equally with 54 % and 46 % for parallel and antiparallel orientations, respectively. This is in contrast with literature value for related compounds favoring the parallel orientation with 75 % Taking the less steric demand of thiophene moieties within 2 into account, the measured torsion angles of the two thiophenes with 65.31° and 67.60° with respect to the phenanthroline plane seem reasonable, which is very similar to previously reported thiophene‐substituted phenanthrolines. Interestingly, in case of even more sterically demanding dimethyl‐substituted thiophenes torsion angles lie in the same region , …”
Section: Resultscontrasting
confidence: 61%
“…Regarding the photophysical properties of phenanthroline complexes, it is well known that substitution of phenanthroline in 3,8‐ and 4,7‐positions significantly influences the photochemistry of coordination complexes as π‐orbital energies are strongly influenced , . In this context, the effects of substituents introduced at 5‐ or 5,6‐position of phenanthroline are far less explored , . This is mainly due to the demanding synthetic procedures in order to access these positions efficiently.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, it has been shown that substituents in the 5-and/or 6-positions have negligible effects on the wavelength of absorption. 28,29 The luminescence spectra of the complexes were recorded in CH 3 CN at room temperature with excitation at the absorption maxima (l max ) of the MLCT bands. The complexes exhibit broad emission manifolds which may be assigned as 3 MLCT phosphorescence, in the 607-611 nm region.…”
Section: Electronic Absorption and Emission Spectral Propertiesmentioning
confidence: 99%
“…The rigid compound cis-1,2-bis(diphenylphosphanyl)ethylene (cis-dppe) has been widely exploited as a bidentate ligand for transition metals. A selection of recent examples include complexes involving iron(II) (Song et al, 2018), copper(I) (Trivedi et al, 2017), gold(I) (Yao & Yam, 2015), nickel(II) (Schallenberg et al, 2014), nickel(III) (Hwang et al, 2015), and palladium(II) and platinum(II) (Song et al, 2017;Oberhauser et al, 1998a). The phosphorus atoms of this ligand have also been modified to give the corresponding oxide, sulfide and selenide derivatives (Morse et al, 2016;Duncan & Gallagher, 1981;Colquhoun et al, 1979;Aguiar & Daigle, 1964).…”
Section: Chemical Contextmentioning
confidence: 99%